A cross cultural investigation of airlines service quality through integration of Servqual and the Kano model. (January 2015) - Basfirinci, Cigdem; Mitra, Amitava
Abstract: This paper examines the service quality attributes of airlines with regard to their effect on customer satisfaction in a cross-cultural context. The applicability of a modified Servqual instrument as a means of measuring customers' perceptions and expectations is explored using respondents from USA and Turkey. The study is unique as it integrates the Servqual scale and the Kano model in a complementary way. The findings reveal that the Servqual gap scores are negative in both USA and Turkey, in all areas of service quality, indicating that customers' perceptions fall far short of their expectations. For the Kano model, it is demonstrated that the general structure of the scale is the same for both countries. However, the two countries differ in certain service quality attributes as far as prioritization. This has implications for the formulation of airline marketing strategies. While some degree of standardization is necessary for certain service elements, especially if the airline is catering for the international market, there are certain service attributes that should be designed to meet local needs and expectations. Highlights: The Servqual scale is used for measuring airline service quality across cultures. The customers' perceptions fall far short of their expectations in both the USA and Turkey. The Turkish sample's perception of airline service quality was lower than for America. A globally standardized service quality solution will be insufficient for airlines. Airlines need to balance standard services with local needs of different markets.